2008
DOI: 10.1002/jccs.200800150
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Liquid‐Solid Flotation Separation of Cadmium by Ammonium Sulfate‐Potassium Iodide‐Cetylpyridine Chloride‐Water System

Abstract: The liquid‐solid flotation separation behaviors of Cd2+ in ammonium sulfate‐potassium iodide‐cetylpyridine chloride‐water system and the conditions for the separation of Cd2+ from other metal ions were studied. The results showed that in the presence of 1.0 g (NH4)2SO4 and when the dosage of 0.1 M potassium iodide was 2.0 mL and 0.01 M cetylpyridine chloride (CPC) solution was 1.0 mL respectively, the formed water‐insoluble ternary association complex of KI‐CPC‐Cd floated above water phase and liquid‐solid pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…pH is one of the important factors which affect the efficiency of retention/elution metal ions by solid phase extraction [25][26][27][28][29]. The effect of pH was studied by varying pH in the range of 3-9.…”
Section: Effect Of Ph On Metal Ion Recoverymentioning
confidence: 99%
“…pH is one of the important factors which affect the efficiency of retention/elution metal ions by solid phase extraction [25][26][27][28][29]. The effect of pH was studied by varying pH in the range of 3-9.…”
Section: Effect Of Ph On Metal Ion Recoverymentioning
confidence: 99%
“…There are meny other methods to separate and enrich Hg(II),such as extraction separation [1][2] , column-chromatographic separation [3] , solid phase extraction separation [4] ,chromatographic separation [5] ,micellar high-performance liquid chromatography [6] .But all the aforesaid methods have used a organic solvent as extractant or need complicated instrumentation. Salt-ternary association complex-water system not only has the advantages of liquid-solid extraction system without organic solvent [7][8] , but also has characteristics such as rapid split-phase rate and clear interface between phases and less reagent.There have been some reports about flotation separation of metal ions by salt-ternary association complex-water system [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…There are meny other methods to separate and enrich Hg(II),such as extraction separation [1][2] , column-chromatographic separation [3] , solid phase extraction separation [4] ,chromatographic separation [5] ,micellar high-performance liquid chromatography [6] .But all the aforesaid methods have used a organic solvent as extractant or need complicated instrumentation. Salt-ternary association complex-water system not only has the advantages of liquid-solid extraction system without organic solvent [7][8] , but also has characteristics such as rapid split-phase rate and clear interface between phases and less reagent.There have been some reports about flotation separation of metal ions by salt-ternary association complex-water system [9][10][11] .In this paper we have studied the flotation separation of mercury(II) by sodium chloridepotassium iodide-octadecyl trimethyl ammonium chloride system.The results showed that in the presence of 0.5 g NaCl,water-insoluble ternary association complex of (OTMAC) could be separated successfully from those metal ions without any masking agent by flotation at pH 3.0. A method of flotation separation of mercury(II) was established,and it has been used for the flotation separation of mercury (II) in the sample of synthetic water with satisfactory results.…”
mentioning
confidence: 99%
“…There are meny other methods to separate and enrich Hg(II),such as extraction separation [1][2] ,column-chromatographic separation [3] , solid phase extraction separation [4] ,chromatographic separation [5] ,micellar high-performance liquid chromatography [6] .But all the aforesaid methods have used a organic solvent as extractant or need complicated instrumentation. Salt-ternary association complex-water system not only has the advantages of liquid-solid extraction system without organic solvent [7][8] , but also has characteristics such as rapid split-phase rate and clear interface between phases and less reagent.There have been some reports about flotation separation of metal ions by salt-ternary association complex-water system [9][10] .…”
Section: Introductionmentioning
confidence: 99%